Chlorambucil–rituximab as first‐line therapy in patients affected by follicular non‐Hodgkin's lymphoma: a retrospective single‐centre study. Issue 4 (22nd July 2014) - Martinelli, Giovanni; Montoro, Juan; Vanazzi, Anna; Andreola, Giovanna; Liptrott, Sarah; Radice, Davide; Negri, Mara; Preda, Lorenzo; Pruneri, Giancarlo; Laszlo, Daniele
Abstract: Rituximab, a chimeric monoclonal antibody directed against the CD20 antigen, has been shown to be active in newly diagnosed and relapsed patients with follicular lymphoma (FL), both as monotherapy and in combination with chemotherapy. Many studies suggest that the prognosis of patients with FL may improve when it is used in combination with chemotherapy. Despite these advances, the disease remains essentially incurable with standard therapy, and novel approaches to treatment are needed because optimal therapy is not defined. The combination of chlorambucil–rituximab is one of several standard treatment options for FL. Here, we considered data arising from 75 patients with newly diagnosed FL at the European Institute of Oncology treated with the combination of rituximab plus chlorambucil. The aim of this study was to evaluate the efficacy and safety of chlorambucil and rituximab, delivered 6 mg/m 2 /day orally for 6 weeks and 375 mg/m 2 in a standard 4‐weekly schedule, respectively. Patients responding to the induction therapy received a prolonged therapy with four additional cycles of chlorambucil plus rituximab. Seventy‐one patients (94.6%) completed the treatment; four patients discontinued treatment because of grade 3–4 hematological toxicity. The overall response rate was 97.3% including 74.7% of complete responses. Only two patients had a stable disease at revaluation after treatment. With a median follow‐up of 57 months, 72 patients (96%) are alive. Median event‐free survival (EFS) and median overall survival (OS) were not reached; 5‐year OS rate was 98.4%. The 5‐year EFS was 71.3%. By univariate and multivariate analyses, elevated beta‐2 microglobulin levels and partial responses to therapy were correlated with worse EFS. These results suggest that the combination of chlorambucil and rituximab is an active and safe regimen in patients with newly diagnosed FL, principally in those with low tumour burden and favourable prognostic factors. Copyright © 2014 John Wiley & Sons, Ltd.